2020
DOI: 10.18632/aging.103475
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a global transcriptional regulatory landscape for early non-small cell lung cancer to identify hub genes and key pathways

Abstract: This study aimed to investigate the potential pathogenesis of early non-small cell lung cancer (NSCLC), including lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), by constructing a global transcriptional regulatory landscape to identify hub genes and key pathways. A total of 1,206 differentially expressed genes (DEGs) in early NSCLC were identified compared to normal lung tissue samples in GSE33532 and GSE29013. DEGs-related protein-protein interaction networks (PPIs) were constructed based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…LUAD and LUSC are the two most common types of NSCLC, and LUSC is the main pathological type of lung malignancy [19][20][21]. Currently, less than 10% of patients with advanced metastatic LUSC can live more than 5 years [22].…”
Section: Discussionmentioning
confidence: 99%
“…LUAD and LUSC are the two most common types of NSCLC, and LUSC is the main pathological type of lung malignancy [19][20][21]. Currently, less than 10% of patients with advanced metastatic LUSC can live more than 5 years [22].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin B1 ( CCNB1 ) binds to specific cyclin-dependent kinases, and these interactions play crucial roles in the cell cycle regulation [ 73 ]. It is well known that CCNB1 is highly expressed in NSCLC and is a potential biomarker for both lung adenocarcinoma [ 74 ] and lung squamous cell carcinoma [ 75 ], belonging to two subtypes of NSCLC. Constructing the CCNB1 -related subnetwork revealed that PRC1 , CEP55 , KIF14 , KIF4A , and HJURP had the highest RWR scores.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the most common chest tumor in the world, with a high incidence and mortality. More than 2.2 million people in the world have been newly diagnosed with lung cancer in 2021, accounting for 11.1% of all newly diagnosed cancer ( Bu et al, 2020 ; Xu et al, 2020 ). Lung squamous cell carcinoma (LUSC), deriving from chronic stimulation and injury of bronchial columnar epithelial cells, takes up a large percentage of lung cancer ( Sánchez Danés and Blanpain, 2018 ).…”
Section: Introductionmentioning
confidence: 99%